2014
DOI: 10.1074/jbc.m114.613653
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inhibition for BMS-791325, a Novel Non-nucleoside Inhibitor of Hepatitis C Virus NS5B Polymerase

Abstract: Background: BMS-791325, a non-nucleoside inhibitor of HCV NS5B, has robust clinical efficacy. Results: Biochemical and biophysical methods revealed a non-competitive time-dependent inhibition mechanism and permitted complete parameterization of inhibitor binding kinetics. Conclusion: Thumb and finger variants affect BMS-791325 association rates. Significance: The impact of NS5B variants on BMS-791325 binding provides insight into the basis of inhibitor resistance and the process of replication complex formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In vitro characterisation of beclabuvir revealed potent activity against HCV in recombinant enzyme assays and cell culture models, however, reduced potency was also observed against GT2, and variable activity against GT6 viruses [ 76 ]. Similar to other molecules binding to T1, P495 substitutions ( Figure 3 ) were associated with increased resistance to beclabuvir [ 76 , 77 ]. However another T1 RAV A421V, was identified upon treatment of GT1 patients with baclabuvir in a phase 2 trial [ 78 ].…”
Section: Hcv Rdrp As a Target For Daasmentioning
confidence: 59%
See 1 more Smart Citation
“…In vitro characterisation of beclabuvir revealed potent activity against HCV in recombinant enzyme assays and cell culture models, however, reduced potency was also observed against GT2, and variable activity against GT6 viruses [ 76 ]. Similar to other molecules binding to T1, P495 substitutions ( Figure 3 ) were associated with increased resistance to beclabuvir [ 76 , 77 ]. However another T1 RAV A421V, was identified upon treatment of GT1 patients with baclabuvir in a phase 2 trial [ 78 ].…”
Section: Hcv Rdrp As a Target For Daasmentioning
confidence: 59%
“…The mechanism of inhibition for the HCV NNIs appears to vary depending on which of the allosteric sites the inhibitor binds to, although structural studies indicate that most NNIs interfere with conformational changes required for an initiation and elongation competent RdRp [ 65 ]. For instance, benzimidazole and indole derivatives (T1), which have been shown to inhibit the initiation of RNA transcription, had no effect once the RdRp-RNA complex was formed, indicating that these molecules act at a step prior to the formation of a productive RdRp-RNA complex, which is time-dependent [ 77 , 106 , 107 ]. Crystallographic analyses revealed that these molecules prevent the formation of intramolecular contacts between thumb and fingers domain, preventing the formation of a productive RdRp-RNA complex [ 108 ].…”
Section: Mechanism Of Action For Rdrp Nnismentioning
confidence: 99%
“…In general, such compounds inhibit the initiation step of RNA replication [54,55] and not the elongation step. Beclabuvir has been shown to equally inhibit de novo and primer dependent synthesis, 5-75 fold more potently than previously studied compounds [56], thus resulting the most effective thumb site 1 inhibitor of genotype 1 (GT-1) NS5B polymerase to our knowledge [57]. After its binding, beclabuvir inhibits NS5B activity in a time-dependent manner [56], and thus prevents the formation of active replication complexes [58].…”
Section: Mechanism Of Actionmentioning
confidence: 97%
“…In in vitro studies, binding assays with NS5B genetic variants (wild type, L30S and P495L) revealed a two-step, slowbinding mechanism of the drug [56]. In detail, resistance substitutions selected by BCV in genotype 1-based replicons mostly mapped to the NS5B amino acid 495 (P495A/S/ L/T) [52], which therefore can be considered the only clinically relevant resistance variant.…”
Section: Resistant Strainsmentioning
confidence: 99%
See 1 more Smart Citation